A Three points bending ultrasonic fatigue resistance and vickers hardness of Tlalpujahua clay thermally treated (Fracture and Structural Integrity, 2025)
Ultrasonic fatigue at an operating frequency of 20 kHz was conducted on thermally treated clay bricks at 500, 750, and 1000 °C with a holding time of 5 h, using a three-point bending setup to assess their fatigue endurance. A Vickers hardness test was also performed on small clay squares thermally treated at the same temperatures, showing increased hardness values. X-ray diffraction (XRD) analysis was also performed, revealing temperature-induced changes in the clay chemical composition. Specifically, the illite transformation into spinel at 1000 °C contributed to a significant increase in hardness and, consequently, a diminution in fatigue life. A finite element simulation under different applied loads was performed to evaluate the von Mises stress behavior of the clay brick. Considering the change in mechanical properties, such as bulk density, at various temperatures. The simulation results show a corresponding behavior with the values of the Vickers hardness. This study provides a perspective on the relationship between ultrasonic fatigue, Vickers hardness, and thermal treatment.
Keywords: Ultrasonic fatigue; Clay; Mechanical properties